Hubungan kesejahteraan psikologis dengan postpartum stress pada ibu - Farhan Hendiansyah; Yosi Dewi Setiowati; Elis Yulia Ningsih (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Postpartum is a critical transition period marked by significant physical and psychological changes that may increase vulnerability to stress. Postpartum stress can interfere with maternal functioning, emotional regulation, and caregiving capacity. Psychological well-being is considered a protective factor that enables mothers to adapt to postpartum challenges. Purpose: To examine the relationship between psychological well-being and postpartum stress among mothers. Method: This study used a quantitative correlational design involving postpartum mothers 2–12 months after delivery. The study was conducted among postpartum mothers residing in the Greater Jakarta area with a postpartum period of 2–12 months, conducted from October 2025 to February 2026. Data were collected using validated psychological well-being and postpartum stress scales. Results: There was no significant relationship between psychological well-being and postpartum stress (r = 0.054, p = 0.569), indicating that the level of psychological well-being was not significantly associated with postpartum stress. Conclusion: No significant relationship was found between psychological well-being and postpartum stress among postpartum mothers. Postpartum stress appears to be more closely associated with situational, biological, and social factors than with psychological well-being. Keywords: Maternal Mental Health; Postpartum Stress; Psychological Well-Being.